ChemInform Abstract: Dimeric Complexes of Rare‐Earth Substituted Keggin‐Type Silicotungstates: Syntheses, Crystal Structure and Solid State Properties. Issue 44 (4th November 2014) - Saini, Mukesh Kumar; Gupta, Rakesh; Parbhakar, Swati; Mishra, Anil Kumar; Mathur, Rashi; Hussain, Firasat
Abstract Compounds (IV) and (VI) are characterized by single crystal XRD, FTIR, UV/VIS, photoluminescence, 13C, and 1H NMR spectroscopy, and vibrating sample magnetometry.